The hallmark and crosstalk of immune cells after intracerebral hemorrhage: Immunotherapy perspectives - Zhang, Wenqing; Wu, Qingyuan; Hao, Shilei; Chen, Shengli (Frontiers in Neuroscience, 2023)
Intracerebral hemorrhage (ICH) is one of the most dangerous types of strokes with a high morbidity and mortality rate. Currently, the treatment of ICH is not well developed, mainly because its mechanisms are still unclear. Inflammation is one of the main types of secondary injury after ICH and catalyzes the adverse consequences of ICH. A large number of immune cells are involved in neuroinflammation, such as microglia, astrocytes, oligodendrocytes, lymphocytes, macrophages and neutrophils. Nevertheless, the characteristics and crosstalk of immune cells have not been fully elucidated. In this review, we endeavor to delve into the respective characteristics of immune cells and their interactions in neuroimmune inflammation, and further elucidate favorable immunotherapeutic approaches regarding ICH, and finally present an outlook.